Development and Validation of a Green Analytical Method for the Determination of Norfloxacin in Raw Material by FTIR Spectrophotometry - Hisano Natori, Jessica Sayuri [UNESP]; Totoli, Eliane Gandolpho [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Aoac Int, 2016)
Norfloxacin is a broad-spectrum antimicrobial agent, widely used in humans and animals for the treatment of urinary tract infections. It is a second-generation fluoroquinolone. Several analytical methods to analyze norfloxacin have been described in the literature. However, most of them are complex and require the use of large amounts of organic solvents. This paper describes the development and validation of a green analytical method for the determination of norfloxacin in raw material by FTIR spectrophotometry. This method does not require the use of organic solvents, minimizing waste generation in the process and its environmental impacts. The development of methods that promote the reduction, prevention, or elimination of waste generation has become highly attractive to the pharmaceutical industry because of the growing demand from civil society and government authorities for environmentally friendly products and services. The FTIR spectrophotometry method was validated according to International Conference on Harmonization guidelines, showing adequate linearity (r=0.9936), precision, accuracy, and robustness. This validated method can be used as an environmentally friendly alternative for the quantification of norfloxacin in raw material in QC routine analysis.